Constrictive pericarditis following mRNA COVID-19 vaccination in a patient with systemic sclerosis. Issue 2 (August 2022) - Misumi, Ikuo; Ogata, Aki; Fukuda, Koichiro; Sato, Koji; Nagano, Miwa; Usuku, Hiroki; Tsujita, Kenichi
Abstract: A 59-year-old man with systemic sclerosis and interstitial pneumonia was referred to our department because he developed dyspnea and leg edema after receiving a first shot of coronavirus disease 2019 (COVID-19) vaccine. Transthoracic echocardiography showed moderate pericardial effusion with conspicuous fibrin deposition. Prednisolone was increased from 6 mg/day for systemic sclerosis to 20 mg/day. Thereafter, pericardial effusion gradually decreased. However, his symptoms continued. Transthoracic echocardiography showed disappearance of pericardial effusion and thickened pericardium. Pulsed-wave and tissue Doppler echocardiography revealed that the patient suffered from newly developed constrictive pericarditis. COVID-19 vaccination might have contributed to acute pericarditis and subsequent constrictive pericarditis in the present case of systemic sclerosis and pulmonary fibrosis. Learning objective: Incidence of adverse effects after coronavirus disease 2019 vaccination is rare. The present case suggests the risk of pericarditis that may lead to constrictive pericarditis.